L’Économie des sens en Inde: Exploration des thèses de Walter Ong - Pinard, Sylvain (Anthropologica, 2022)
A number of Indologists have underlined the preponderance of the sense of sight in India, and shown how vision informs diverse notions and social behaviour. However, it is apparent in light of other sources that the sense of taste, including everything that surrounds the exchange of food, also occupies a prominent place in the culture, which we cannot ignore ?gustation is the paradigmatic "integrative mechanism" of social groups. Moreover, the central role played by touch introduces an indeniable element of proximity in sharing into the culture, in contrast to the stress on distance and individualism in Western schemes of perceptions and society. Following up on Walter Ong’s thesis concerning the senses as shapers and bearers of culture, the author undertakes to study the work of each of the senses in Hindu society, partly with the view to testing [and nuancing] Ong’s thesis, and partly so as to better delimit which of the senses is dominant in the Hindu cultural context.